Missionaris Zaman Kolonial di Tanah Batak: Refleksi Urgensi Komunikasi Dakwah Indegenous - Muhamad Fajri (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2021)
Throughout the history of human civilization,communication has always been an urgent matter in carrying out the existence and fulfillment of human needs in the form of physical or non-physical. Communication is a tool to convey something, so da'wah also uses communication as a tool to convey message of Islamic da'wah to mad'u (the object of da'wah). Da'wah was first started in Arabia by Muhammad SAW. Since Islamis rahmatallil'alamiin (a blessing for whole the world),of course in the spread of da'wah to the earth (apart from Arabic) will meet different cultures from mad'u. The purpose of this study was to analyze the history of the failure and success of  Christian missionaries in Batak land from communication perspective. The research method was based on library research by conducting a critical analysis of the source and then reflecting on Islamic da'wah in the context of communication rather than theology. The result of this study revealed that the failure and success of three Christian missionaries in Batak land was due to communication problems. Two people were killed because they did not master the culture and communication of destination area,and one person succeeded because he had mastered cross-cultural communication. Then, this is reflected in Islamic da'wah that both of missionaries and da'wah convey messages to others in the context of communication. Therefore, indigenous da'wah communication is needed in conveying da'wah to others.